Análise da qualidade da água em municípios afetados pela Usina Hidrelétrica de Belo Monte - RODRIGUES, Madson Andrey Pereira (2025)
Water is indispensable for all living beings, in addition to being the basis of ecosystems, it becomes a source that will soon become extinct if it is used irrationally and unsustainably. Energy megaprojects like Belo Monte present predictable challenges, such as population growth, loss of biodiversity and changes in water quality. The dumping of untreated sewage into the Xingu River represents a threat to water quality, causing a series of problems that affect not only the environment, but also public health and the local economy. Therefore, bacteriological assessment of water plays an essential role in preventing waterborne diseases. This work aimed to analyze the water quality of the Xingu River, in three municipalities: Altamira, Vitória do Xingu and Senador José Porfírio. For this, some limnological parameters were analyzed, such as: Hydrogen Potential (pH), Turbidity, Water Temperature and electrical conductivity; And for microbiological parameters: Escherichia coli and total coliforms. In the analysis of the physicochemical parameters, at all points, the data obtained were within the limits established by the CONAMA resolution, for class 2 freshwaters. However, the microbiological aspects for total Coliforms and E. coli are outside the parameters considered acceptable by CONAMA no. 357/2005. In this way, the installation of the hydroelectric plant revealed a worrying reality in relation to water quality in areas under the direct influence of this large project, highlighting the urgency of effective actions to improve basic sanitation infrastructure, reduce water pollution and protect the health of the population that depends on these water resources.